Kritik Orientalis terhadap Hadis: Atas Pemikiran Ignaz Goldziher dan Joseph Schacht - Rijal Khoirul Anam; Bagus Damar Galih Permadi (Research Institute and Community Engagement of UIN MADURA, 2026)
This study systematically examines the thoughts of Ignaz Goldziher and Joseph Schacht in orientalist criticism of the authenticity of hadith through a literature review (Systematic Literature Review) based on the PRISMA guidelines to filter 11,705 articles into 40 relevant studies (n = 40). The main objectives include: (1) mapping Schacht's theory of skepticism projecting back, argumentum e silentio, and common link as well as Goldziher's sanad-matan criticism approach, (2) comparing the points of agreement and differences in Schacht's focus on legal hadith versus Goldziher's on the social construction of the post-Prophet hadith corpus, and (3) evaluating the implications for contemporary hadith studies. The results show the dominance of qualitative studies based on library research (Â±90%), with the consensus that both figures open up space for methodological dialogue even though they are often accused of being selective and reductive in their choice of sources. Theory mapping reveals the strengths and weaknesses of each Schacht excels in historical sanad analysis, Goldziher emphasizes the socio-political context while contemporary academic responses emphasize the integration of classical sanad-matan verification with matan analysis and Western historical-philological frameworks. This study recommends the development of an interdisciplinary framework, the involvement of empirical data, and the expansion of non-English literature to enrich modern hadith studies in an inclusive and contextual manner.